Oxidative stress signaling in the pathogenesis of diabetic cardiomyopathy and the potential therapeutic role of antioxidant naringenin - Nan Xu; Siqi Liu; Yongqiang Zhang; Yujing Chen; Yumei Zuo; Xiaoqiu Tan; Bin Liao; Pengyun Li; Jian Feng (Taylor & Francis Group, 2023)
ABSTRACTDiabetes mellitus (DM) is one of the most prevalent metabolic disorders that poses a global threat to human health. It can lead to complications in multiple organs and tissues, owing to its wide-ranging impact on the human body. Diabetic cardiomyopathy (DCM) is a specific cardiac manifestation of DM, which is characterized by heart failure in the absence of coronary heart disease, hypertension and valvular heart disease. Given that oxidative stress is a key factor in the pathogenesis of DCM, intervening to mitigate oxidative stress may serve as a therapeutic strategy for managing DCM. Naringenin is a natural product with anti-oxidative stress properties that can suppress oxidative damage by regulating various oxidative stress signaling pathways. In this review, we address the relationship between oxidative stress and its primary signaling pathways implicated in DCM, and explores the therapeutic potential of naringenin in DCM.